Assessment of national program of learning regions in Slovakia: Design and testing - Stanislav Kološta; Lenka Sabelová; Pavol Král' (DANUBE: Law, Economics and Social Issues Review, 2018)
In May 2007, the Ministry of Education, Science, Research and Sport of the Slovak Republic approved the National Program for Learning Regions. It states that the long-term strategic objective for the development of Slovak regions is the gradual reduction of disparities in living standards in regions and to improve regional economic performance. One of the tools for achieving this goal is considered the learning region concept. The main aim of this article is to streamline the presentation and monitoring of the partial progress made in achieving the objectives of the National Program for Learning Regions in the Slovak Republic to policy-makers and to make this relatively complex issue accessible to a wider audience through one aggregated index and two partial indices; the PCA method was used. The results showed relatively large differences between regions. The highest value of the aggregated LR index was reached by the Trnava region, followed by the Bratislava region; these two regions seems to be in accordance with reaching the objectives of the National Program for Learning Regions. The lowest values were found in the Banská Bystrica, Preésov and Koésice regions. Moreover, we found a positive correlation between aggregated and economical-innovative indices with average GDP during the years 2008-2014 at the NUTS 3 level.
Keywords: 330; Learning Region; Principal Component Analysis; Index; Assessment; Regional Development; Indicator